Hypercholesterolemia diagnosis, treatment patterns, and 12-month target achievement in clinical practice in Germany in patients with familial hypercholesterolemia - Gitt, Anselm Kai; Laufs, Ulrich; März, Winfried; Paar, W. Dieter; Bramlage, Peter; Marx, Nikolaus; Parhofer, Klaus G. (Journal of Clinical Medicine, 2022)
BACKGROUND: Familial hypercholesterolemia (FH) is a highly prevalent disorder and a risk factor for early coronary artery disease. The objective of this registry was to document the clinical characteristics of patients with definite FH in Germany and to document lipid profiles, lipid-lowering therapy, and lipid target achievement during longitudinal follow-up. - METHODS: HYDRA-FH was a national, prospective, multicenter, non-interventional registry conducted in 35 centers in Germany. Consecutive adult patients with definite FH were included (n = 241). - RESULTS: In the cross-sectional analysis (n = 233), lipid-lowering therapy involved statins (82.0%), ezetimibe (31.8%), and PCSK9 antibodies (18.5%); 11.2% of patients were receiving no lipid-lowering drugs. Median lipid levels were: low-density lipoprotein cholesterol (LDL-C) 134 mg/dL (3.5 mmol/L), high-density lipoprotein cholesterol (HDL-C) 48 mg/dL (1.2 mmol/L), triglycerides 160 mg/dL (1.9 mmol/L), total cholesterol 211 mg/dL (5.5 mmol/L). Values were above the normal threshold (150 mg/dL) for LDL-C in 72.9%, total cholesterol in 29.7%, and triglycerides in 45.0% of patients. After the 12-month follow-up (n = 145), only 17.2% had LDL-C < 70 mg/dL, and 20.7% had either LDL-C < 70 mg/dL or a reduction of ≥50% versus baseline. - CONCLUSION: This study provides insight into the clinical characteristics and current treatment status of patients with FH in Germany. Many patients with FH do not achieve recommended lipid levels.
Gesehen am 17.08.2022